A randomized trial to evaluate a complex, co-created, culture-sensitive intervention to promote healthy lifestyles and compliance to therapy in immigrants with type 2 diabetes: A protocol of a multicenter Italian study - Laura Bonvicini; Francesco Venturelli; Francesca Bononi; Giulietta Luul Balestra; Giusy Iorio; Luca Ghirotto; Alessio Petrelli; Silvia Pierconti; Giovanna Laurendi; Maria Perticone; Alessio Pellegrino; Maria Boddi; et al. (PLoS ONE, 2025)
Introduction The active involvement of end users may overcome socio-economic, cultural and context-related barriers that may reduce health promotion effectiveness in type 2 diabetes control and prevention. The “Cardio-metabolic diseases in immigrants and ethnic minorities: from epidemiology to new prevention strategies” (DIABETHIC) project funded by the European Union through the Italian Ministry of Health includes a multicentre randomised controlled trial (RCT) aimed to assess the effectiveness of a co-created health promotion intervention for immigrants affected by type 2 diabetes. This protocol describes the co-creation process and methodological challenges in evaluating co-created health promotion interventions. Methods and analysis Between November 2023 and July 2024, four Italian primary care centres will recruit 200 immigrants with type 2 diabetes that will be randomised to usual health promotion practice or to the experimental health promotion intervention developed through a participatory process. Endpoints are changes in glycated haemoglobin, Body Mass Index, diet, physical activity and therapeutic adherence at 12 months after recruitment. Qualitative research experts supported the participatory process at local and national levels. According to available evidence and recommendations, the participatory process focused on the three pillars of type 2 diabetes control (diet, physical activity, and therapeutic adherence). To co-create the intervention, interviews, focus groups and role-plays were conducted with patients and immigrants, healthcare workers and representatives of social services. Identified barriers were ranked according to priority and actionability. Given different health promotion practice in the four centres, the intervention was standardised by function (dietary counselling, culturally tailored information materials, access to cultural mediation, training in effective and reflective communication, individual and group meetings) rather than by form (operators involved, protocols and timeframes), which was defined locally by feasibility and by contrasting usual health promotion. (Trial registration: ClinicalTrials.gov ID NCT06131411).